2021
DOI: 10.3390/cancers13153884
|View full text |Cite
|
Sign up to set email alerts
|

Streamlined Schemes for Dosimetry of 177Lu-Labeled PSMA Targeting Radioligands in Therapy of Prostate Cancer

Abstract: (Background) Aim of this retrospective analysis was to investigate in mCRPC patients treated with [177Lu]Lu-PSMA-617 whether the absorbed dose (AD) in organs at risk (OAR, i.e., kidneys and parotid glands) can be calculated using simplified methodologies with sufficient accuracy. For this calculation, results and kinetics of the first therapy cycle were used. (Methods) 46 patients treated with 2 to 6 cycles of [177Lu]Lu-PSMA-617 were included. As reference (current clinical standard) full dosimetry of the OAR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
19
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 56 publications
7
19
2
Order By: Relevance
“…time point is more favorable if smaller range of variations in PD against TIA ref are preferred (Figure 3A, left, and Figure 4A, middle). Our results agree with those reported by Kurth et al (26) who applied the STP prior approach for cycles 2 to 6, and found differences in AD of ±6% for kidneys and ±10% for parotid glands when using a single SPECT at 48h p.i. of 177 Lu-PSMA-617 compared to MTP.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…time point is more favorable if smaller range of variations in PD against TIA ref are preferred (Figure 3A, left, and Figure 4A, middle). Our results agree with those reported by Kurth et al (26) who applied the STP prior approach for cycles 2 to 6, and found differences in AD of ±6% for kidneys and ±10% for parotid glands when using a single SPECT at 48h p.i. of 177 Lu-PSMA-617 compared to MTP.…”
Section: Discussionsupporting
confidence: 93%
“…In this work, we aimed at comparing STP against MTP image-based dosimetry methods, which could increase adoption in the clinical environment. STP dosimetry methods have been studied predominantly for 177 Lu-DOTATATE therapy (13,(21)(22)(23), but also for 177 Lu-PSMA therapy (24)(25)(26). Three different approaches for STP dosimetry have been proposed: 1) using population based mean T 1/2 eff (27),…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since we previously showed that for this patient cohort, tracer uptake kinetics in organs are comparable to those in metastasized castrate-resistant prostate cancer (mCRPC) patients [ 14 ], we postulate that the results of this study could be translated to dosimetry in mCRPC patients as well. This is also supported by recent findings of comparable studies in this patient population [ 30 33 ]. For lesion dosimetry, a two-time point protocol is proposed; so, no general kinetics apart from a single compartment distribution are assumed.…”
Section: Discussionsupporting
confidence: 90%
“…Various studies have demonstrated the use of simplified dosimetry calculation methodologies for potential clinical adaptation. Recent work reported on two simplified [ 177 Lu]Lu-PSMA-617 dosimetry schemes for organs at risk, whereby one method simplified image acquisition and the other, dose calculation [60]. The simplified schemes were found to be feasible and showed potential for simplification in future works, and were both consistent with their reference method for cumulative absorbed dose.…”
Section: Methods Of Dosimetry Calculationmentioning
confidence: 97%